Quantum Algorithms - M. Dalzell, Alexander; McArdle, Sam; Berta, Mario; Bienias, Przemyslaw; Chen, Chi-Fang; Gilyén, András; T. Hann, Connor; J. Kastoryano, Michael; T. Khabiboulline, Emil; Kubica, Aleksander; Salton, Grant; Wang, Samson; et al. (Cambridge University Press, 2026)
This book provides a comprehensive, up-to-date survey of quantum algorithms and how they connect to practical, concrete applications of quantum computing. Its modular, encyclopedic structure facilitates usage as a reference for researchers. This title is also available as Open Access on Cambridge Core.